1984
DOI: 10.1007/bf00290382
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal endothelial release of fibrinolytic activity and fibronectin in diabetic microangiopathy

Abstract: Endothelial cell function in Type 1 (insulin-dependent) diabetic patients, both with and without retinopathy, was assessed by measuring the plasma fibrinolytic activity and fibronectin after 10 min venous stasis induced by a sphygmomanometer cuff. After venous stasis, diabetic subjects with proliferative retinopathy had fibrinolytic responses (median 0.13 increasing to 0.26 U/ml) in the low normal range, which were significantly less (p less than 0.005) than control subjects (0.17-0.68 U/ml) and diabetic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…24,28,29,32 Our findings suggest that smoking does not significantly compromise non-specific endothelial cell function in diabetes prior to the development of advanced complications.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…24,28,29,32 Our findings suggest that smoking does not significantly compromise non-specific endothelial cell function in diabetes prior to the development of advanced complications.…”
Section: Discussionmentioning
confidence: 80%
“…In this context it is reassuring that evidence exists to support the prolonged maintenance of normal fibrinolysis in the setting of uncomplicated disease. 24,31 It seems safe to conclude that the impairment of fibrinolysis associated with smoking is circumvented in Type 1 DM; that levels of the principal activator and inhibitor of fibrinolysis are normal in uncomplicated Type 1 DM, and that breakfast and exogenous insulin do not significantly alter t-PA or PAI-1 levels.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A diminished fibrinolytic activity, especially in patients with angiopathy, was described 223 ' 226 ' 228 and also after venous occlusion. 229 Although the fibrinolytic activity was increased after venous occlusion, high molecular weight fibrinogen split products were found by Gurewich et al 224 in patients with diabetic macro-and microangiopathy. In another study, the tissue plasminogen activator of the vessel wall was reduced.…”
Section: Fibrinolysismentioning
confidence: 93%
“…3-q22. Previous studies in subjects with type 1 diabetes have shown an enhanced fibrinolytic activity and lower levels of PAI-1 with diabetic retinopathy. 95,96 Altered PAI-1 expression, through its effect on plasmin production and tissue proteolysis, may alter the endothelial extracellular matrix composition and accumulation seen in diabetic microvascular disease. 97 The Pima Indians of Arizona have an extremely high incidence of diabetes which is exclusively non-insulin-dependent and complications of diabetes are similar in nature to those seen in other populations with type 2 diabetes.…”
Section: Plasminogen Activator Inhibitor 1 (Pai-1)mentioning
confidence: 99%